‘Affiliate Marketer’ Advertising Fraud: A Normative Legal and Prophetic Hadith Perspective - Baharuddin, Mochammad Achwan; Latifatur Rokhmah Adhami; Wardatun Nadhiroh (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to explore the transformative impact of influencer marketing on the marketplace, altering consumer behaviour and marketing strategies. Social media platforms have become pivotal as businesses promote products and services with influencers. However, the integrity of some influencers is compromised due to the allure of high sales bonuses, leading to deceptive practices. The primary focus of this study is to examine the existence of influencers within the framework of Normative Law and Prophetic Hadith, shedding light on their involvement in fraudulent activities. Employing discourse analysis with a statutory and conceptual approach, the research positions influencers and affiliate marketing programs on par with conventional advertising companies. It becomes evident that Normative Law, specifically Law No. 8 of 1999, offers limited provisions, primarily centered around consumers' rights to accurate and transparent information concerning the goods being traded. On the other hand, fraudulent acts committed by influencers potentially fall under the purview of Law Number 11 of 2008 concerning Information and Electronic Transactions [as last amended by Law No. 19 of 2016]. Moreover, the Hadith of Muslim history strictly prohibits sellers from engaging in manipulative buying and selling practices, including any misdirection of product information.